Evaluation of the Efficacy of CD101, a Novel Echinocandin, in the Treatment of Candida auris Infection Using a Murine Model of Disseminated Candidiasis. (4th October 2017) - Hager, Christopher; Long, Lisa; Larkin, Emily; Ghannoum, Mahmoud
Abstract: Background: The first case of an invasive infection caused by C. auris was reported in July of 2016. Multiple cases have since been reported with high mortality rates due to the multidrug-resistant nature of C. auris . Although C. auris shows increased susceptibility to the echinocandin class of antifungals, the use of these drugs is restricted to multiple IV administrations. CD101 is a novel echinocandin with enhanced stability and pharmacokinetics, allowing for once weekly high dose administration. In this study, we evaluated the efficacy of CD101 in the treatment of disseminated C. auris infection using a murine model of disseminated candidiasis. Methods: Female 6–8 week old CD-1 mice were immunosuppressed with cyclophosphamide (200 mg/kg) 3 days prior to infection and 150 mg/kg 1 day post-infection. On the day of infection, mice were inoculated with 3 x 10 7 C. auris blastospores via the lateral tail vein. Mice were randomized into 5 groups ( n = 5 for colony forming units (CFU) and n = 10 for survival): CD101 20 mg/kg administered by intraperitoneal (IP) injection, fluconazole 20 mg/kg administered per os (PO), amphotericin B 0.3 mg/kg IP, and a vehicle control. Treatments were administered 2 hours post-infection (day 1) and again on day 4 of the study for a total of 2 doses. Mice were monitored daily and a survival curve was generated. CFU groups were sacrificed on day 8 of the study. One kidney was removed from each mouse, homogenized, plated on potato dextrose agar (PDA), and incubated at 35°C for 2 days to determine CFU. The remaining survival mice were monitored until the end of the study (day 14). Results: CD101 showed an average 3 log reduction in kidney CFU compared with fluconazole, amphotericin B, and vehicle treated groups, which was statistically significant ( P = 0.03, 0.03, and 0.04, respectively). At the end of the study, percent survival of mice in CD101, fluconazole, amphotericin B, vehicle, and untreated groups was 80, 0, 30, 20, and 0%, respectively (Figure 1). Conclusion: Taken together, our findings show that CD101 possesses potent antifungal activity against C. auris infection in a disseminated model of candidiasis. Additionally, treatment with CD101 resulted in a significantly higher overall percent survival. Further investigation of this drug is warranted. Disclosures: M. Ghannoum, Amplyx Pharmaceuticals: Consultant, Research Contractor and Scientific Advisor, Consulting fee and Research grant; Cidara Therapeutics: Consultant and Research Contractor, Consulting fee and Research grant